Outpatient Management of Headache after Pediatric Emergency Department Visit: Are we Missing Anything?. Issue 9 (26th July 2019) - Glatstein, Miguel; Voliovitch, Yair; Orbach, Rotem; Carmi, Amit; Amarilyo, Gil; Carbell, Gary; Rimon, Ayelet
Abstract : Background: Headache is a common complaint in children at a pediatric emergency department (PED). The primary objective of this analysis is to describe the outcome of patients presenting with headache to the PED and discharged with neurology follow up. The secondary objective is to describe the diagnostic evaluation children with headache underwent in the PED and to evaluate headache characteristics which are more likely associated with serious, life‐threatening conditions. Methods: A retrospective chart review of children who were discharged from the PED after evaluation for headache, with a scheduled urgent neurology outpatient clinic follow up at the same institution, over a 3.5‐year period. Results: During the study period, we identified 300 children whose admitting diagnosis was headache and they were discharged from the PED with a scheduled follow up. None of these patients had papilledema on fundoscopy performed by an ophthalmologist during the PED visit. Following neurology outpatient clinic visit, 62 (21%) were referred to perform brain magnetic resonance imaging. None of the patients had a diagnosis of brain tumor or any anatomic abnormality that could increase intracranial pressure. Conclusions: No immediate life‐threatening cases presented to the follow up neurology clinic for evaluation. A scheduled urgent neurology outpatient clinic follow up in any child with headache who is discharged from the PED, offers a safety net, even when the physical examination including fundoscopy is normal.